Nitrogen stabilizes the wurtzite polymorph in ZnSe1−xTex thin films. Issue 42 (12th October 2022) - Culman, Theodore H.; Woods-Robinson, Rachel; Mangum, John S.; Smaha, Rebecca W.; Rom, Christopher L.; Zakutayev, Andriy; Bauers, Sage R.
Abstract : Phase-pure wurtzite structure is observed in ZnSe1− x Te x thin films doped by flowing molecular nitrogen during growth. A combination of factors help stabilize this phase and the result opens the door to new polymorph engineering in II–VI materials. Abstract : Materials based on tetrahedral structural motifs are the most used semiconductor systems in deployed technologies. This holds true for microelectronics based on doped Si (diamond structure), photovoltaics based on CdTe (zinc blende structure), and light emitting diodes based on GaN (wurtzite structure). In these compound examples, the extended crystal structure is determined by modifications to the arrangement of the underlying tetrahedral motifs; controlling this structure is a foundational way to design functionality in semiconductor materials. Here, N-doped ZnSe1− x Te x thin films are grown by RF sputtering from compound targets with N2 gas as a N source. Crystalline films form across a large range of growth conditions, and in some N-doped films there is a transformation from the usual zinc blende structure to wurtzite. Depending on the temperature and N2 flow rate during growth, wurtzite can be synthesized across most of the composition range explored, ranging from Te-rich ( x ≈ 0.7) to nearly pure ZnSe ( x ≈ 0.1). Synchrotron diffraction data show that the wurtzite is phase-pure at N-doped ZnSe0.5 Te0.5 alloy compositions grown under some conditions. Temperature-dependent resistivity measurements collected from N-doped ZnSe0.5 Te0.5 are well fit by a model dominated by variable range hopping, suggesting defect-mediated transport. Density functional theory calculations that show that dilute N concentrations help stabilize the wurtzite polymorph of ZnSe0.5 Te0.5 . Electron microscopy reveals voids in the N-doped films' microstructures. We attribute this more open microstructure—which may also be partially responsible for stabilizing the wurtzite phase—to trapped N2 . This work highlights unexpected polytypism in one of the most studied semiconductor systems, motivating a closer look at other semiconductor alloys for similar structural diversity.